The Elephant in The Room: AML Relapse Post Allogeneic Hematopoietic Cell Transplantation - Abou Dalle, Iman; Atoui, Ali; Bazarbachi, Ali (Frontiers in Oncology, 2022)
Relapsed acute myeloid leukemia (AML) following allogeneic hematopoietic cell transplantation (allo-HCT) is an unfavorable event associated with a poor prognosis, particularly for patients with early relapses. It usually arises from resistant leukemic blasts that escaped both preparative chemotherapy regimen and the graft-versus-leukemia (GVL) effect. Independent from the choice of salvage treatment, only minority of patients can achieve durable remissions. In recent years, better understanding of the disease relapse biology post allo-HCT allowed the application of newer strategies that could induce higher rates of remission, and potential longer survival. Those strategies aim at optimizing drugs that have a direct anti-leukemia activity by targeting different oncogenic mutations, metabolism pathways or surface antigens, and concurrently enhancing the immune microenvironment to promote GVL effect. This review discusses the current treatment landscape of AML relapse post allo-HCT.